Science and technology in China : implications and lessons for India - Edited by Maharajakrishna Rasgotra; Rasgotra, Maharajakrishna (ed.) (New Delhi Sage, 2013)
Science and Technology in China discusses the changing structural and institutional context of scientific research in China. The new environment of global competition entails that the norms of generation of new knowledge are as important as those for innovation and commercialization. China has been able to achieve this in a largely state-controlled environment, where political will and commitments have played an increasingly important role. India, on the other hand, is still caught in a paradox of too much democracy at all levels of social and economic activity. It needs a big political push and inclusive decentralized approach to realize its well-defined plans and objectives to make its international presence felt.
Keywords: IFS as an editor; Indian Foreign Service